The effects of spirituality and moral intensity on ethical business decisions: a cross-sectional study - Anderson, Stephen E. ca. 20./21. Jh. (Journal of business ethics, 2021)
We present a cross-sectional study of ethical decision-making correlated with spirituality and utilizing moral intensity as a moderator for workers in the Southeastern United States (N = 117). This study presents spirituality as an individual variable and moral intensity as a situational variable along with ethical decision-making to examine the interaction of these factors in moral dilemmas. Utilizing previously validated instruments for ethical decision-making and individual spirituality, we find that workers with relatively high measured spirituality made less ethical decisions compared to workers with relatively lower measures of spirituality. Further, we find that the introduction of high moral intensity as a situational variable does not moderate the observed correlation between spirituality and ethical decision-making. This research supports the conceptual nature of the Interactionist Theory by presenting in a single study both individual and situational variables in ethical decision-making.